2023
DOI: 10.3389/fmicb.2023.1137701
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of DSS-induced colitis in mice by a new-isolated Lactobacillus acidophilus C4

Abstract: IntroductionProbiotic is adjuvant therapy for traditional drug treatment of ulcerative colitis (UC). In the present study, Lactobacillus acidophilus C4 with high acid and bile salt resistance has been isolated and screened, and the beneficial effect of L. acidophilus C4 on Dextran Sulfate Sodium (DSS)-induced colitis in mice has been evaluated. Our data showed that oral administration of L. acidophilus C4 remarkably alleviated colitis symptoms in mice and minimized colon tissue damage.MethodsTo elucidate the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…IBD is a representative intestinal disease with increasing prevalence worldwide [ 1 ]. Recent studies show that probiotics such as Lactobacillus species are a safe treatment for IBD; indeed, data suggest that probiotics improve colitis in the DSS-induced mouse model and IBD patients by regulating the intestinal barrier, immune responses, and gut microbiota [ 36 , 37 ]. Recently, we demonstrated that the probiotic strain HY7718 suppresses inflammatory responses and maintains TJs between intestinal epithelial cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…IBD is a representative intestinal disease with increasing prevalence worldwide [ 1 ]. Recent studies show that probiotics such as Lactobacillus species are a safe treatment for IBD; indeed, data suggest that probiotics improve colitis in the DSS-induced mouse model and IBD patients by regulating the intestinal barrier, immune responses, and gut microbiota [ 36 , 37 ]. Recently, we demonstrated that the probiotic strain HY7718 suppresses inflammatory responses and maintains TJs between intestinal epithelial cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic LAB have been demonstrated to exert positive effects on the anti-oxidative 10 , anti-inflammatory 34 , and anticancer activities 35 . The antioxidant capabilities of probiotics have been evaluated through IC 26 , CFS 10 and CFE or their metabolites in vitro 36 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some beneficial bacteria can improve colitis symptoms. This is the case with the Lactobacillus / Lactococcus group, where several members can alleviate DSS-induced colitis symptoms [ 63 ]. Our observation that YM consumption reduced Eubacterium rectale / Clostridium coccoides and Enterobacteriaceae groups and increased the Lactobacillus / Lactococcus group could in part explain the beneficial properties of the medicinal plant since controlling dysbiosis and stimulating the presence of favorable bacteria could improve colitis symptoms [ 64 ].…”
Section: Discussionmentioning
confidence: 99%